Synthesis of Key Intermediate of Rocaglamide via SmI2 Catalyzed Intramolecular Reductive Coupling Reaction - Wang1, Xianyou; Gong1, Dongjun; Qin2, Zhaohai (Asian Journal of Chemistry, 2014)
The compound of methyl 8b-hydroxy-6,8-dimethoxy-3a-(4-methoxyphenyl)-1-oxo-3-phenyl-2,3,3a,8a-tetrahydrocyclopenta[b]-benzofuran-2-carboxylate (3b), can be obtained with moderate yields under optimum reaction conditions. During this optimization, intramolecular ketone-ester reductive coupling reactions promoted by SmI2 have been studied. The synthetic procedure was successfully applied to the preparation of the key intermediate of the rocaglamide.